Grain boundary engineering for crack bridging: A new model for intergranular stress corrosion crack (IGSCC) propagation - Engelberg, D; Marrow, T; Newman, R; Babouta, L (Elsevier, 2008)
This chapter introduces a new intergranular stress corrosion crack (IGSCC) propagation model based on grain bridging by crack resistant, low energy grain boundary, (GB), and their related triple junction density (TJD). A stochastic model considers the frequency of immune GBs with respect to the microstructural probability of arresting a crack at a TJ. This is reflected in the maximum critical crack length, and influencing factors such as grain size and total probability of crack arrest. The observation of grain bridging has suggested a new approach of predicting intergranular stress corrosion crack length distributions. The key premise of this model is that bridges arise from the local arrest at "cul-de-sac" (2-CSL TJ) or unfavorably orientated triple junctions (1-CSL TJ). Crack arrest by a single junction is not expected to significantly affect the behavior of a crack with a size greater than several grains. The cumulative effect of grain bridging gives rise to a shielding stress, which reduces the stress intensity factor at the crack tip. Several microstructure dependent factors lead to the shielding stress. First, the number of bridges per unit area is assumed to vary in proportion to the resistance factor. Second, the bridge size, and thus its contribution to the shielding stress, depends on the grain size, which is related to the spacing of effective TJs. Finally, the degree of shielding is assumed to build up and then saturate at steady state with increasing crack length. © 2008 Elsevier Ltd All rights reserved.